Comparing student motivations for and emotional responses to national standardised tests and internal school tests: The devil in the detail. Issue 1 (April 2022) - Dowley, Mark; Rice, Suzanne
National testing of students has become an increasingly prevalent policy tool, often implemented to drive improvement through increased accountability and heightened competition between schools. Such testing has been found to generate negative emotional responses among students, including increased stress and anxiety . However, there is little examining whether such responses are associated specifically with national testing regimes or are more general responses to testing situations. This study surveyed 206 students in Australian secondary schools to compare responses to NAPLAN and internal school tests. Students reported higher expectations for their performance in internal school tests than for NAPLAN, higher levels of boredom for NAPLAN and greater levels of confidence for their internal school tests. While most students reported low levels of negative emotional responses to NAPLAN, a small group of students reported strong negative emotional responses to both NAPLAN and internal school tests, suggesting that negative responses to national testing programs may be more dependent on the individual student.